ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL KIA PICANTO (STUDI PADA KONSUMEN KIA PICANTO DI DEALER KIA MOBIL DINAMIKA SEMARANG) - Yuniar Silvia Silaen; Wahyu Hidayat; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
Brand equity elements such as brand awareness, perceived quality, brand associations and brand loyalty is believed to influence purchasing decisions Kia Picanto car. The purpose of this study was to determine the effect of brand awareness, perceived quality, brand associations and brand loyalty on purchasing decisions. This type of research is the explanation (explanatory research). The sampling technique used is purposive sampling of the 75 respondents who are consumers Kia Picanto The Kia Car Dealer Dynamics Semarang. Data was collected through questionnaires and interviews. Then performed a quantitative analysis of the data obtained as: validity and reliability, simple regression test, multiple regression analysis, hypothesis testing via t test and F-test, correlation coefficients and coefficients of determination (R2). The result of this study is that all the independent variables, namely brand awareness (X1), perceived quality (X2), brand association (X3), and brand loyalty (X4) together (simultaneously) or individually affect the dependent variable purchase decisions . Suggestions in this research that the company is able to increase the number of cars Kia Picanto sales with sales promotion and improvement of the service is good service, especially in the procurement of spare parts that do not take a long time. In addition, technological improvements in order to make products more fuel efficient Kia Picanto and establish the relationship with customers to increase sales of Kia Picanto car.